Beyond Stunting: Mechanisms Linking Length to Early Child Development Among Infants in Rural India (P10-003-19). (13th June 2019) - Black, Maureen; Yimgang, Doris; Hurley, Kristen; Harding, Kimberly; Fernandez-Rao, Silvia; Balakrishna, Nangalla; Radhakrishna, Kankipati; Reinhart, Gregory; Nair, Krishanpillai
Abstract: Objectives: In low and middle-income countries, early child development (ECD) is associated with stunting, but the association with length-for-age z-scores (LAZ) is understudied. The objective is to examine whether the association with ECD among infants extends beyond stunting to LAZ and whether it is altered by nurturance or inflammation. Methods: Sample: 513 infants (mean age 8.6 months, SD 2.2), 20% stunted (LAZ < -2) participated in a randomized controlled trial of micronutrient powder (MNP) in rural India. Following baseline, infants were re-evaluated at 6- and 12-months. LAZ was calculated from measured length, inflammation (C-reactive protein, CRP) from blood draw; nurturance from home observation (HOME Inventory), and ECD from Mullens Early Learning Scale (visual reception, fine/gross motor and receptive/expressive language). Linear mixed effects models were conducted, accounting for repeated measures and clustering, adjusted for child age, anemia, maternal education, household assets, and intervention. LAZ interactions with CRP and HOME scores were tested. Results: LAZ was significantly positively associated with all ECD domains over time. HOME was positively associated with visual reception and expressive language (Table 1). HOME interactions were marginal for fine motor ( P  = 0.058) and significant for receptive language ( P  = 0.015). For HOME scores < -1 SD, LAZ was positively related to fine motor and receptive language, for HOME scores >1 SD, LAZ was not related to ECD (Figure 1). CRP was not related to ECD and CRP interaction was not significant. Conclusions: The positive association between LAZ and ECD illustrates vulnerability prior to the threshold of stunting. Maternal nurturance is positively associated with multiple domains of infants' ECD and attenuates relations between LAZ and receptive language and fine motor. Inflammation (measured by CRP) is not associated with ECD. Linear growth within normal and nurturant caregiving are needed to promote ECD. Funding Sources: Mathile Institute for the Advancement of Human Nutrition, Nutrition International, Sackler Institute for Nutrition Science of the New York Academy of Sciences.